Aerosol Delivery of Lung Surfactant and Nasal CPAP in the Treatment of Neonatal Respiratory Distress Syndrome - Walther, Frans J.; Waring, Alan J. (Frontiers in Pediatrics, 2022)
After shifting away from invasive mechanical ventilation and intratracheal instillation of surfactant towards non-invasive ventilation with nasal CPAP and less invasive surfactant administration in order to prevent bronchopulmonary dysplasia in preterm infants with respiratory distress syndrome, fully non-invasive surfactant nebulization is the next Holy Grail in neonatology. Here we review the characteristics of animal-derived (clinical) and new advanced synthetic lung surfactants and improvements in nebulization technology required to secure optimal lung deposition and effectivity of non-invasive lung surfactant administration. Studies in surfactant-deficient animals and preterm infants have demonstrated the safety and potential of non-invasive surfactant administration, but also provide new directions for the development of synthetic lung surfactant destined for aerosol delivery, implementation of breath-actuated nebulization and optimization of nasal CPAP, nebulizer circuit and interface. Surfactant nebulization may offer a truly non-invasive option for surfactant delivery to preterm infants in the near future.